THE IMPACTS OF OIL PRICE VOLATILITY ON STRATEGIC INVESTMENT OF OIL COMPANIES IN NORTH AMERICA, ASIA, AND EUROPE - Zhu,Qianqian (2016)
ABSTRACT The crude oil price volatility plays an essential role for the oil companies when making a strategic investment decision. Different economic and political backgrounds could drive oil companies in North America, Asia, and Europe to make different strategic investment decision. Real options methodology is applied in analyzing the impact of oil price volatility on strategic investment of oil companies in the three regions. The empirical results show that the regional differences do exist, where the relationship between oil price volatility and oil companies' strategic investment in North America shows a reverse U shaped curve; meanwhile in Asia is exhibits a U shaped curve; while that in Europe shows a positive correlated linear relationship. These different regional results of oil price uncertainty could provide companies and governments essential information to make investment and policy decisions based on the according regions.